The Effect of Stirring Speeds to the Entrapment Efficiency in a Nanoparticles Formulation of Java Plum’s seed Ethanol Extract (Syzygium cumini) - Widayanti Supraba; Yohanes Juliantoni; Agus Dwi Ananto (The University of Mataram, 2021)
Java Plum’s (Syzygium cumini) seed contains flavonoids in the form of quercetin. Quercetin plays an essential role in stimulating insulin production from pancreatic beta cells. However, it could be easily degraded by gastric acid or the digestive system. Thus, in this research, a good delivery system for quercetin will be established, namely nanoparticles. The study objectives are determining the entrapment efficiency’s percentage of nanoparticle preparations from ethanol extracts of Java Plum’s seeds as well as observing the effect of stirring speed on the percentage of entrapment efficiency. Java Plum’s seed extract was obtained by maceration method using ethanol 70% with the ratio between the simplicial powder and solvent is 1 : 4 respectively. Meanwhile, the solvent evaporation process was undergone by using a water bath with temperature not exceeding 70°C. The nanoparticle formulation of Java Plum’s seed extract was made by adding polymers in the form of chitosan and sodium tripolyphosphate cross-linker with three variations of stirring speed (500, 1000, and 1500 rpm) using a magnetic stirrer. The percentage of entrapment efficiency was obtained by subtracting the flavonoids levels of Java Plum’s seeds extract and flavonoids levels of Java Plum’s seeds extract in nanoparticles. Then, the value was divided by flavonoids levels of Java Plum’s seeds extract and multiplied by 100%. Quercetin levels obtained by absorbance readings using spectrophotometry UV-Visible, then absorbance value added into variable X on equation quercetin’s standard curve y = 0,0229x + 0,0644. The results show that the percentage of entrapment efficiency at speed variations of 500, 1000, and 1500 rpm are 48.8459%, 49.1064%, and 56.0413% respectively. According to the t-test two independent samples statistical test, the data has a 0.961 probability value (500 rpm vs 1000 rpm), 0.324 probability value (1000 rpm vs 1500 rpm), 0.25 (500 rpm vs 1500 rpm). Probability value > 0.05, which means the stirring speed does not significantly influence the percentage of entrapment efficiency.